Polyimide film and laminate plate made using same

By using a copolymerized polyimide film of copolymerized segments composed of BPDA and PDA, the problem of insufficient conjunction force during the metallization process is solved, and the high conjunction force effect is achieved under high temperature conditions.

CN119463491APending Publication Date: 2025-02-18TAIMIDE TECH INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310997840.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing polyimide films are insufficient in the metallization process, and it is difficult to produce a thinner polyimide layer and metal laminated body under high temperature hot pressing conditions.

Method used

Used from 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), phenylastic tetracarboxylic anhydride (PMDA), p-phenylasediamine (p-PDA), 2,2'-dimethyl -4,4'-diaminobiphenyl (m-TB) and 4,4'-diaminodiphenyl ether (ODA) are used to form copolymerized segments with BPDA and PDA to improve the film's Thermal properties and retention.

Benefits of technology

It is achieved that the metallization adhesion force of the polyimide film is increased without using the primer coating, and the adhesion force is maintained at aging conditions of 150°C greater than 0.5 kgf/cm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004385306840000221
    Figure BDA0004385306840000221
  • Figure BDA0004385306840000231
    Figure BDA0004385306840000231
Patent Text Reader

Abstract

The invention discloses a polyimide film and a laminated plate thereof, and particularly relates to a polyimide film containing a 3, 3 ', 4, 4'-biphenyl tetracarboxylic dianhydride (BPDA) component; a pyromellitic dianhydride (PMDA) component; a p-phenylenediamine (p-PDA) component; a component of 2, 2 '-dimethyl-4, 4'-diaminobiphenyl (m-TB) and a component of 4, 4 '-diaminodiphenyl ether (ODA), and a component of 2, 2'-dimethyl-4, 4 '-diaminobiphenyl (m-TB); and the polyimide film and the laminated plate using the BPDA and the PDA as copolymerization chain segments have good thermal properties, mechanical properties and adhesiveness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polyimide films, and in particular to a polyimide film and a laminate made using the film. Background Art

[0002] Flexible circuit board is a base body between metal layer and polyimide. Most flexible circuit boards have a layer of glue between the metal layer and the polyimide layer as a medium between the two layers. In recent years, as the design of flexible circuits has developed towards fine lines, the thickness of the metal layer has become thinner and thinner, so a laminate with a polyimide layer and a metal layer directly bonded has been developed.

[0003] Generally speaking, when bonding a polyimide layer to a metal layer, a plastic polyimide layer can be attached to the polyimide layer as a bonding medium. However, during the bonding process with the metal, it is necessary to undergo high-temperature hot pressing. This method makes it difficult to produce a thinner polyimide layer and metal laminate. Another method is to use direct metallization to bond the metal layer to the polyimide layer. However, common polyimides are difficult to bond to metal layers, and surface treatment is required before metallization to ensure a certain degree of bonding with the metal.

[0004] TWI695865 proposes a method for improving the adhesion after metallization. The method is to apply a layer of primer on the polyimide film to improve the adhesion between the metal layer and the polyimide layer. However, due to the poor thermal properties of the primer coating, the thermal properties of the entire polyimide film will be reduced, and the primer layer is prone to sticking, making the subsequent processing difficult.

[0005] Therefore, the present application proposes a polyimide film that can provide good adhesion without primer coating, which can effectively improve the adhesion of the polyimide film after metallization and can still maintain adhesion greater than 0.5kgf / cm after baking at 150°C for 24 hours under aging conditions. Summary of the invention

[0006] In order to solve the above-mentioned deficiencies in the art, the present application aims to provide a polyimide film and a laminate made using the film, particularly a polyimide film and a laminate made using the film, which comprises a 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) component; a pyromellitic anhydride (PMDA) component; a p-phenylenediamine (p-PDA) component; a 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB) component and a 4,4'-diaminodiphenyl ether (ODA) component; and which uses BPDA and PDA as copolymer segments, so that the polyimide film and the laminate made using the film have good thermal properties, mechanical properties and adhesion.

[0007] The present application is a polyimide film, which is a copolymerized polyimide formed by dianhydride and diacid.

[0008] The dianhydride comprises 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) accounting for 60-80 mol% of the total dianhydride moles and pyromellitic anhydride (PMDA) accounting for 20-40 mol% of the total dianhydride moles;

[0009] The diamines include p-phenylenediamine (p-PDA) accounting for 10-40 mol% of the total diamine moles, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB) accounting for 30-60 mol% of the total diamine moles, and 4,4'-diaminodiphenyl ether (ODA) accounting for 10-40 mol% of the total diamine moles;

[0010] The copolymerized polyimide has a copolymerized segment composed of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) and p-phenylenediamine (p-PDA), and the copolymerized segment accounts for 25-40% of the total molar number of the polyimide, so that the thermal linear expansion coefficient CTE of the polyimide film is less than 15ppm / ℃ and the Young's modulus is greater than 7GPa. DETAILED DESCRIPTION

[0011] The technical solution of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0012] It is particularly important to point out that similar substitutions and modifications made to the present application are obvious to those skilled in the art, and they are all deemed to be included in the present application. Relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present application to implement and apply the technology of the present application. Obviously, the described embodiments are only some embodiments of the present application, not all embodiments.

[0013] If no specific conditions are specified in this application, the preparation shall be carried out under conventional conditions or the conditions recommended by the manufacturer. The raw materials or excipients used, as well as the reagents or instruments used, for which the manufacturers are not specified, are all conventional products that can be obtained commercially.

[0014] The application is described in detail below.

[0015] Polyimide film production

[0016] The polyimide film is made of a copolymerized polyamic acid by chemical cyclization or thermal cyclization. The copolymerized polyamic acid is obtained by polymerization of a dianhydride and a diamine. The dianhydride includes 3,3',4,4'-biphenyltetracarboxylic anhydride (BPDA) accounting for 60-80 mol% of the total dianhydride mole and pyromellitic anhydride (PMDA) accounting for 20-40 mol% of the total dianhydride mole; the diamine includes p-phenylenediamine (p-PDA) accounting for 10-40 mol% of the total diamine mole, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB) accounting for 30-60 mol% of the total diamine mole and 4,4'-diaminodiphenyl ether (ODA) accounting for 10-40 mol% of the total diamine mole. The copolymerized polyimide needs to have a copolymer segment composed of 3,3',4,4'-biphenyltetracarboxylic anhydride (BPDA) and p-phenylenediamine (p-PDA).

[0017] The implementation method is to use BPDA and PDA to react in a solvent for 1 to 3 hours to form a copolymer segment, and the molar number of the copolymer segment must account for 25% to 40% of the total molar number to ensure better thermal properties.

[0018] As solvents, dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), γ-butyrolactone (GBL), and N,N-dimethylformamide (DMF) can be used to prepare the polyimide component. In the present application, dimethylacetamide is used as the solvent.

[0019] After the polymerization of the copolymer segments of BPDA and PDA is completed, the remaining diamine is added. The diamine can be added in whole or in part to form the second copolymer segment or the third copolymer segment.

[0020] The diamine can be any one of mTB, ODA, and PDA. After the diamine is added, PMDA or BPDA is added to adjust the total anhydride molar ratio to the total diamine molar ratio to 0.95 or more, and the reaction is stirred for at least 1 hour, preferably more than 2 hours, and then a small amount of BPDA or PMDA is used to adjust the viscosity. Finally, the solution is adjusted to 100,000cps to 600,000cps, preferably 150,000 to 400,000cps. At this time, the solid content of the solution can be between 10 and 25wt%, and the preparation of the polyimide precursor is completed.

[0021] In addition, the above-mentioned polyimide precursor can be added with inorganic material particles or organic material particles for the purpose of improving various properties such as winding, sliding, thermal conductivity, high hardness, color, etc. The inorganic material particles can be silicon oxide, boron nitride, aluminum oxide, titanium oxide, zirconium oxide, zinc oxide, calcium phosphate, etc.

[0022] The organic material particles may be tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer (PFA), polytetrafluoroethylene (PTFE), liquid crystal polymer (LCP), or polyimide (PI).

[0023] The average particle size of the inorganic material particles and the organic material particles is usually 0.01um to 100um, preferably 0.03um to 10um, and more preferably 0.05um to 5um.

[0024] The addition amount of inorganic material particles and organic material particles is 0.5-10%, preferably 1-3%.

[0025] The polyimide precursor (copolyamic acid) can be imidized to prepare a polyimide film by a thermal cyclization method or a chemical cyclization method.

[0026] The thermal cyclization method is a cyclization method that does not use a dehydrating agent or a catalyst. The copolymerized polyamic acid is mixed with a solvent, the viscosity is adjusted to 8,000 to 20,000 cps, and then coated on a glass or metal carrier. The mixture is heated to a temperature range of 350 to 400 degrees and baked for a long time. After the baking time is 1 to 8 hours, a polyimide film is obtained.

[0027] The chemical cyclization method is to mix the copolymerized polyamic acid with a solvent to adjust the viscosity, and then add a catalyst and a dehydrating agent for chemical cyclization, wherein the dehydrating agent can be acetic anhydride or benzoic anhydride, and acetic anhydride is selected as the dehydrating agent in this application; wherein the catalyst can be pyridine, 3-methylpyridine, 2-methylpyridine, 4-methylpyridine, isoquinoline, quinoline, triethylamine, wherein the preferred choice is pyridine, 3-methylpyridine, 2-methylpyridine, 4-methylpyridine, and 3-methylpyridine is selected as the catalyst in this application.

[0028] The above catalyst and dehydrating agent can be used alone or mixed with a solvent for dilution.

[0029] Add to the mixed solution, stir the mixed solution mixed with dehydrating agent and catalyst evenly, and then use centrifugal degassing machine to degas. Apply the degassed solution to the glass plate and then use a scraper to apply it. The scraper gap can be adjusted according to the required thickness. Place the coated sample at 40℃~120℃ and bake for 10~40 minutes, preferably 60℃~100℃ for 20~30 minutes, then bake at 170℃~200℃ for 10 minutes, then bake at 230℃~280℃ for 5~25 minutes, preferably 240℃~260℃ for 10~20 minutes, and finally bake at 330℃~400℃ for 10~30 minutes as the final treatment, preferably 350℃~370℃ for 15~20 minutes.

[0030] In addition to glass, a metal plate can also be used as the substrate in the above film-making process. When the metal plate is used to make the imide film, it needs to be removed from the metal plate after being baked and dried in the temperature range of 40°C to 120°C. The removed semi-dried film is fixed on a metal frame, and then the temperature is raised to 170°C and baked for 20 minutes, and then the temperature is raised to 350°C and baked for 20 minutes as a final treatment to obtain a polyimide film.

[0031] Laminate production

[0032] The method of laminating a board includes: forming a nickel metal layer on the surface of a polyimide film by electroless plating so that the nickel metal layer contacts the polyimide film; and after the nickel metal layer is formed, performing heat treatment and then forming a copper layer thereon by electrolytic plating.

[0033] In the present application, the nickel layer is formed by chemical plating on one or both sides of the polyimide substrate. As for chemical plating, it can be a known chemical plating method, and there is no particular limitation. In addition, as for a specific example of chemical plating, the polyimide film can also be subjected to surface hydrophilization treatment first, and here, the surface treatment known in the technical field can be used, and there is no limitation here.

[0034] The surface treatment used in this application uses a roll-to-roll plasma processor (model R2RP03) purchased from Creating NanoTechnologies Inc. to perform surface hydrophilization treatment on the polyimide film. The operating conditions are described as follows.

[0035] The polyimide film is fixed on the roll bar and connected to the film guide. The chamber is closed and nitrogen (N2) is introduced. The power is turned on to start exhausting. After the machine is preheated, it can enter the process section. The tension is set to 2kg, the working pressure is 300mTorr, and the power is 10kW. The gas type and flow rate are adjusted. There are four types of gases, namely nitrogen (N2), oxygen (O2), carbon tetrafluoride (CF4) and argon (Ar). They can be combined as needed. The total gas flow rate is controlled between 1900sccm and 2700sccm. The length of the plasma zone is 11m. The processing time can be controlled by adjusting the machine line speed, which ranges from 0.5m / min to 6.0m / min. After the process is completed, oxygen (O2) and argon (Ar) are introduced in sequence to clean the chamber. After breaking the vacuum, the power is turned off, and then the chamber is opened to take out the polyimide film to complete the surface plasma modification.

[0036] This application refers to the SLP metallization process (SLP process) of Japan Okuno Pharmaceutical Co., Ltd., and uses the SLP series of electroless nickel plating reagents to successively perform charge adjustment, pre-immersion, catalysis, acceleration, reduction nickel plating and other steps. The operating conditions are described as follows.

[0037] The hydrophilized PI substrate was immersed in a 65°C SLP-200 solution for 75 seconds for charge adjustment, and then taken out and washed with water.

[0038] The substrate was immersed in a 25°C SLP-300 solution for 25 seconds and a 25°C SLP-400 solution for 75 seconds to allow the catalyst to adhere to the surface of the transparent substrate. The substrate was then taken out and washed with water.

[0039] Then, the samples were immersed in a 35°C SLP-500 solution for 75 seconds to activate the catalyst, and then taken out and washed with water.

[0040] Finally, immerse in SLP-660 solution at 40℃, control the pH value to 8.5±0.1, react for 250 seconds, take out and wash with water, and the nickel metal layer / polyimide film composite film is completed, and the thickness of the single-sided nickel layer is between 0.08 and 0.10μm.

[0041] The copper layer of the present application is not particularly limited, as long as it can form a copper layer for subsequent etching circuits. In addition, in one embodiment of the present application, it is preferred to plate the copper layer on the nickel metal layer by electroplating. The electroplating solution used for the copper layer can be a commercial product, such as copper sulfate electroplating solution (purchased from Jiwei Industrial Co., Ltd.), etc. The operating conditions are described as follows.

[0042] The composite film of the nickel metal layer / polyimide film is first heat-treated at 120°C for 24 hours, and then 2wt% sulfuric acid is used to remove the oxide layer on the surface of the nickel metal layer. Then, electrolytic plating is performed in a plating tank. The plating solution contains 150g / L sulfuric acid, 120g / L copper sulfate and 50ppm chloride ions, as well as appropriate amounts of plating additives such as brighteners and flattening agents. The current density is 4ASD, and the average plating speed is about 0.5μm / min. By controlling the power-on time, a copper metal layer with a thickness of 0.2 to 20μm can be deposited on the surface of the nickel layer as required.

[0043] Example

[0044] <Detection method>

[0045] The thermal and electrical properties of the polyimide films obtained in the following examples were measured using the following methods.

[0046] (1) Young's film thickness: measured according to ASTM D882 standard specification using a Hounsfield H10K-S tensile testing machine.

[0047] (2) Thermal expansion coefficient CTE: According to ASTM D696, the thermal expansion coefficient of the transparent polyimide film was measured using a Q400 TMA instrument produced by TA Instruments. The thermal expansion coefficient of the transparent polyimide film was measured at 50-200°C, and the heating rate was set to 10°C / min. In order to remove the stress caused by the heat treatment, the residual stress was removed by the first measurement, and the second measurement result was used as the actual value.

[0048] (3) Adhesion: measured using a Hounsfield H10K-S tensile testing machine in accordance with IPC-TM-6502.4.9 standard.

[0049] <Example 1>

[0050] Preparation of polyimide film

[0051] 7.139 g of p-phenylenediamine (p-PDA, 0.066 mole) was added to 400 g of N,N-dimethylacetamide (DMAc). After it was completely dissolved, 15.538 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.165 mole) was added. The mixture was stirred for 1 hour while the temperature was maintained at 25°C. 25.694 g of 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB, 0.121 mole) was added and stirred until it was completely dissolved. Then 11.999 g of pyromellitic anhydride was slowly added. (PMDA, 0.055 mole), stirred for 0.5 hour to dissolve and react, and the temperature of the solution was maintained at 25°C, then 12.301 g of BPDA was added and reacted for 1 hour, and then 6.609 g of ODA (ODA, 0.033 mol) was added, and after it was completely dissolved, 19.747 g of BPDA (0.0671 mol) was added, and after stirring and reacting for 2 hours, a small amount of BPDA was used to adjust the viscosity to 250,000±300,000 cps, and finally a copolymer polyamide acid solution with a solid content of 20% was obtained.

[0052] Take out 33 grams of the above copolymerized polyamic acid solution and add 17 grams of N, N-dimethylacetamide (DMAc) to dilute the solid content to 13.2%. After stirring for 10 minutes, dilute acetic anhydride and DMAc at a weight ratio of 5 to 1, and then dilute 3-methylpyridine and DMAc at a weight ratio of 1 to 1. Then add 7.12 grams of acetic anhydride dilution and 5.41 grams of 3-methylpyridine dilution respectively. After uniform stirring, use a centrifugal degasser to degas, apply the degassing solution to the glass plate, and then use a scraper with a gap of 600μm to apply. Place the coated sample in an 80℃ oven for 40 minutes, then heat it to 170℃ at a rate of 3.6℃ / min and bake it for 10 minutes, then heat it to 260℃ at a rate of 5.9℃ / min and bake it for 10 minutes, and finally heat it to 350℃ at a rate of 8.13℃ / min and bake it for 20 minutes as the final treatment.

[0053] Laminate production

[0054] A nickel metal layer is formed on the surface of a polyimide film by electroless plating so that the nickel metal layer contacts the polyimide film; after the nickel metal layer is formed, heat treatment is performed and then a copper layer is formed thereon by electrolytic plating.

[0055] In the present application, the nickel layer is formed on one or both sides of the polyimide substrate by chemical plating. As for chemical plating, it can be a known chemical plating method, and there is no particular limitation. In addition, as for a specific example of chemical plating, the polyimide film can be first subjected to surface hydrophilization treatment, and here, the surface treatment known in the technical field can be used, and there is no limitation here.

[0056] In the present application, the nickel layer is formed by chemical plating on one or both sides of the polyimide substrate. The present application refers to the SLP metallization process (SLP process) of Japan Okuno Pharmaceutical Co., Ltd., and uses the SLP series of electroless nickel plating reagents to sequentially perform charge adjustment, pre-immersion, catalysis, acceleration, reduction nickel plating and other steps. The operating conditions are described as follows.

[0057] The hydrophilized PI substrate was immersed in a 65°C SLP-200 solution for 75 seconds for charge adjustment, and then taken out and washed with water.

[0058] The substrate was immersed in a 25°C SLP-300 solution for 25 seconds and a 25°C SLP-400 solution for 75 seconds to allow the catalyst to adhere to the surface of the transparent substrate. The substrate was then taken out and washed with water.

[0059] Then, the samples were immersed in a 35°C SLP-500 solution for 75 seconds to activate the catalyst, and then taken out and washed with water.

[0060] Finally, the film was immersed in a 40°C SLP-660 solution, the pH value was controlled at 8.5±0.1, and after reacting for 250 seconds, it was taken out and washed with water to complete the nickel metal layer / polyimide film composite film, and the thickness of the single-sided nickel layer was between 0.08 and 0.10 μm.

[0061] The copper layer operating conditions are described as follows:

[0062] The composite film of the nickel metal layer / polyimide film is first heat-treated at 120°C for 24 hours, and then 2wt% sulfuric acid is used to remove the oxide layer on the surface of the nickel metal layer. Then, electrolytic plating is performed in a plating tank. The plating solution contains 150g / L sulfuric acid, 120g / L copper sulfate and 50ppm chloride ions, as well as appropriate amounts of plating additives such as brighteners and flattening agents. The current density is 4ASD, and the average plating speed is about 0.5μm / min. By controlling the power-on time, a copper metal layer with a thickness of 0.2 to 20μm can be deposited on the surface of the nickel layer as required.

[0063] <Example 2>

[0064] Preparation of polyimide film

[0065] 7.167 g of p-phenylenediamine (p-PDA, 0.0663 mole) was added to 400 g of N,N-dimethylacetamide (DMAc). After it was completely dissolved, 17.551 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.165 mole) was added. The mixture was stirred for 1 hour while the temperature was maintained at 25°C. Then 18.762 g of 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB, 0.088 mole) was added. The mixture was stirred until it was completely dissolved. Then 12.047 g of pyromellitic anhydride (PM DA, 0.055 mole), stirred for 0.5 hour to dissolve and react, and the temperature of the solution was maintained at 25°C, then 7.150 g of BPDA was added and reacted for 1 hour, and then 13.272 g of 4,4'-diaminodiphenyl ether (ODA, 0.066 mol) was added, and after it was completely dissolved, 23.076 g of BPDA (0.0784 mol) was added, and the reaction was stirred for 2 hours, and then a trace amount of BPDA was used to adjust the viscosity to 250,000±300,000 cps, and finally a copolymer polyamic acid solution with a solid content of 20% was obtained.

[0066] Take out 33 grams of the above copolymerized polyamic acid solution and add 17 grams of N, N-dimethylacetamide (DMAc) to dilute the solid content to 13.2%. After stirring for 10 minutes, dilute acetic anhydride and DMAc at a weight ratio of 5 to 1, and then dilute 3-methylpyridine and DMAc at a weight ratio of 1 to 1. Then add 7.15 grams of acetic anhydride dilution and 5.43 grams of 3-methylpyridine dilution. After uniform stirring, use a centrifugal degasser to degas, apply the degassed solution to a glass plate, and then use a scraper with a gap of 600μm to apply it. Place the coated sample in an 80℃ oven and bake for 40 minutes, then heat it to 170℃ at a rate of 3.6℃ / min and bake it for 10 minutes, then heat it to 260℃ at a rate of 5.9℃ / min and bake it for 10 minutes, and finally heat it to 350℃ at a rate of 8.13℃ / min and bake it for 20 minutes as the final treatment.

[0067] Preparation of laminated board: same as Example 1

[0068] <Example 3>

[0069] Preparation of polyimide film

[0070] 7.167 g of p-phenylenediamine (p-PDA, 0.0663 mole) was added to 400 g of N,N-dimethylacetamide (DMAc). After it was completely dissolved, 18.526 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.0552 mole) was added. The mixture was stirred for 1 hour while the temperature was maintained at 25°C. 18.762 g of 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB, 0.0884 mole) was added. The mixture was stirred until it was completely dissolved. Then 12.047 g of pyromellitic acid was slowly added. Anhydride (PMDA, 0.0552 mole) and 8.45 g BPDA were stirred for 1 hour, and then 13.272 g of 4,4'-diaminodiphenyl ether (ODA, 0.0663 mole) was added. After all of them were dissolved, 20.801 g of BPDA (0.0707 mole) was slowly added and stirred for 12 hours to allow them to dissolve and react. The temperature of the solution was maintained at 25°C, and then a small amount of BPDA was used to adjust the viscosity to 250,000±300,000 cps, and finally a copolymer polyamide acid solution with a solid content of 20% was obtained.

[0071] Take out 33 grams of the above-mentioned copolymerized polyamic acid solution and add 17 grams of N, N-dimethylacetamide (DMAc) to dilute the solid content to 13.2%. Stir for 10 minutes, then dilute acetic anhydride and DMAc at a weight ratio of 5 to 1, and then dilute 3-methylpyridine and DMAc at a weight ratio of 1 to 1. Then add 7.15 grams of acetic anhydride dilution and 5.43 grams of 3-methylpyridine dilution. After uniform stirring, use a centrifugal degassing machine to degas, apply the degassed solution to a glass plate, and then use a scraper with a gap of 600μm to apply it. Place the coated sample in an 80℃ oven for 20 minutes, then heat it to 170℃ at a rate of 1.8℃ / min and bake it for 20 minutes, then heat it to 350℃ at a rate of 2.0℃ / min and bake it for 20 minutes as the final treatment.

[0072] <Example 4>

[0073] Preparation of polyimide film

[0074] 7.228 g of p-phenylenediamine (p-PDA, 0.0668 mole) was added to 400 g of N,N-dimethylacetamide (DMAc). After it was completely dissolved, 18.683 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.0635 mole) was added. The mixture was stirred for 1 hour while the temperature was maintained at 25°C. 18.921 g of 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB, 0.209 mole) was added and stirred until it was completely dissolved. Then 14.579 g of pyromellitic anhydride (PMD A, 0.0668 mole), stirred for 0.5 hour to dissolve and react, and the temperature of the solution was maintained at 25°C, then 5.244 g of BPDA was added and reacted for 1 hour, and then 13.384 g of 4,4'-diaminodiphenyl ether (ODA, 0.0668 mol) was added, and after it was completely dissolved, 20.977 g of BPDA (0.0713 mol) was added, and the reaction was stirred for 2 hours, and then a trace amount of BPDA was used to adjust the viscosity to 250,000±300,000 cps, and finally a copolymer polyamic acid solution with a solid content of 20% was obtained.

[0075] Take out 33 grams of the above copolymerized polyamic acid solution and add 17 grams of N, N-dimethylacetamide (DMAc) to dilute the solid content to 13.2%. After stirring for 10 minutes, dilute acetic anhydride and DMAc at a weight ratio of 5 to 1, and then dilute 3-methylpyridine and DMAc at a weight ratio of 1 to 1, and then add 7.21 grams of acetic anhydride dilution and 5.48 grams of 3-methylpyridine dilution respectively. After uniform stirring, use a centrifugal degasser to degas, apply the degassing solution to the glass plate, and then use a scraper with a gap of 600μm to apply. Place the coated sample in an 80℃ oven and bake for 40 minutes, then heat it to 170℃ at a rate of 3.6℃ / min and bake it for 10 minutes, then heat it to 260℃ at a rate of 5.9℃ / min and bake it for 10 minutes, and finally heat it to 350℃ at a rate of 8.13℃ / min and bake it for 20 minutes as the final treatment.

[0076] Preparation of laminated board: same as Example 1

[0077] <Example 5>

[0078] Preparation of polyimide film: Same as Example 4

[0079] Production of laminated board: Surface electrochemical modification of polyimide film, fix the polyimide film on the roll bar and connect the film guide, set the tension to 2kg, the working pressure to 300mTorr, the power supply to 10kW, adjust the nitrogen flow to 2000sccm, the length of the plasma zone to 11m, and the line speed to 5.0m / min; after the process is completed, oxygen (O2) and argon (Ar) are introduced in sequence to clean the chamber, and the power is turned off after breaking the vacuum, and then the chamber is opened to take out the polyimide film, and the surface plasma modification is completed. The subsequent steps are the same as in Example 1.

[0080] <Example 6>

[0081] Preparation of polyimide film

[0082] 7.290 g of p-phenylenediamine (p-PDA, 0.0674 mole) was added to 400 g of N,N-dimethylacetamide (DMAc). After all the solution was dissolved, 18.842 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.064 mole) was added. The mixture was stirred for 1 hour and the temperature was maintained at 25°C. Then 19.082 g of 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB, 0.0899 mole) was added and stirred until the mixture was completely dissolved. Then 17.155 g of pyromellitic anhydride (PMDA, 0.0786 mole) was slowly added and stirred for 0.5 hour until the mixture was dissolved and reacted. The temperature of the solution was maintained at 25°C. Then 1.983 g of BPDA was added and reacted for 0.5 hour before ODA was added. 13.499 g (ODA, 0.0674 mol), after it is completely dissolved, add 21.156 g BPDA (0.0719 mol), stir and react for 2 hours, then use a small amount of BPDA to adjust the viscosity to 250,000±300,000 cps, and finally obtain a copolymer polyamic acid solution with a solid content of 20%.

[0083] Take out 33 grams of the above copolymerized polyamic acid solution and add 17 grams of N, N-dimethylacetamide (DMAc) to dilute the solid content to 13.2%. After stirring for 10 minutes, dilute acetic anhydride and DMAc at a weight ratio of 5 to 1, and then dilute 3-methylpyridine and DMAc at a weight ratio of 1 to 1, and then add 7.27 grams of acetic anhydride dilution and 5.52 grams of 3-methylpyridine dilution respectively. After uniform stirring, use a centrifugal degasser to degas, apply the degassing solution to the glass plate, and then use a scraper with a gap of 600μm to apply. Place the coated sample in an 80℃ oven and bake for 40 minutes, then heat it to 170℃ at a speed of 3.6℃ / min and bake it for 10 minutes, then heat it to 260℃ at a speed of 5.9℃ / min and bake it for 10 minutes, and finally heat it to 350℃ at a speed of 8.13℃ / min and bake it for 20 minutes as the final treatment.

[0084] Preparation of laminated board: same as in Example 1.

[0085] <Example 7>

[0086] Preparation of polyimide film: Same as Example 6

[0087] Preparation of laminated board: Surface electrochemical modification of polyimide film, fix the polyimide film on the roll bar and connect the film guide, set the tension to 2kg, the working pressure to 300mTorr, the power supply to 10kW, adjust the nitrogen flow to 2000sccm, the length of the plasma zone to 11m, and the line speed to 5.0m / min; after the process is completed, oxygen (O2) and argon (Ar) are introduced in sequence to clean the cavity, and the power is turned off after breaking the vacuum, and then the cavity is opened to take out the polyimide film to complete the surface plasma modification. The subsequent steps are the same as in Example 1. The subsequent steps are the same as in Example 1.

[0088] <Example 8>

[0089] Preparation of polyimide film: Same as Example 6

[0090] Preparation of laminated board: The polyimide film is surface-modified, fixed on a roll and connected to a film guide, the tension is set to 2kg, the working pressure is 300mTorr, the power supply is 10kW, the argon (Ar) flow rate is adjusted to 2000sccm, the length of the plasma zone is 11m, and the line speed is 5.0m / min; after the process is completed, oxygen (O 2) The chamber is cleaned with argon (Ar), the power is turned off after breaking the vacuum, and then the chamber is opened to take out the polyimide film, and the surface plasma modification is completed. The subsequent steps are the same as in Example 1.

[0091] <Example 9>

[0092] Preparation of polyimide film

[0093] 9.925 g of p-phenylenediamine (p-PDA, 0.0918 mole) was added to 400 g of N,N-dimethylacetamide (DMAc). After it was completely dissolved, 24.304 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.0826 mole) was added. The mixture was stirred for 2 hours while the temperature was maintained at 25°C. Then 19.486 g of 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB, 0.0918 mole) was added. The mixture was stirred until it was completely dissolved. Then 1 7.517 g of pyromellitic anhydride (PMDA, 0.0803 mole) was stirred for 1 hour to dissolve and react, and the temperature of the solution was maintained at 25°C, and then 9.189 g of ODA (ODA, 0.0459 mol) was added. After it was completely dissolved, 18.566 g of BPDA (0.0631 mol) was added. After stirring and reacting for 2 hours, a small amount of BPDA was used to adjust the viscosity to 250,000±300,000 cps, and finally a copolymer polyamide acid solution with a solid content of 20% was obtained.

[0094] Take out 33 grams of the above copolymerized polyamic acid solution and add 17 grams of N, N-dimethylacetamide (DMAc) to dilute the solid content to 13.2%. After stirring for 10 minutes, dilute acetic anhydride and DMAc at a weight ratio of 5 to 1, and then dilute 3-methylpyridine and DMAc at a weight ratio of 1 to 1, and then add 7.42 grams of acetic anhydride dilution and 5.64 grams of 3-methylpyridine dilution respectively. After uniform stirring, use a centrifugal degasser to degas, apply the degassing solution to the glass plate, and then use a scraper with a gap of 600μm to apply it. Place the coated sample in an 80℃ oven and bake for 40 minutes, then heat it to 170℃ at a speed of 3.6℃ / min and bake it for 10 minutes, then heat it to 260℃ at a speed of 5.9℃ / min and bake it for 10 minutes, and finally heat it to 350℃ at a speed of 8.13℃ / min and bake it for 20 minutes as the final treatment.

[0095] Preparation of laminated board: same as in Example 1.

[0096] <Comparative Example 1>

[0097] Preparation of polyimide film

[0098] 11.090 g of p-phenylenediamine (p-PDA, 0.1025 mole) was added to 400 g of N,N-dimethylacetamide (DMAc). After it was completely dissolved, 24.138 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.082 mole) was added. The mixture was stirred for 1 hour while the temperature was maintained at 25°C. Then 19.352 g of 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB, 0.0912 mole) was added. The mixture was stirred until it was completely dissolved. Then 12.427 g of DMAc was slowly added. 0.057 mol of PMDA (0.057 mol) was added and stirred for 0.5 hours to dissolve and react, and the temperature of the solution was maintained at 25°C. Then 6.845 g of 4,4'-diaminodiphenyl ether (0.0342 mol) was added. After it was completely dissolved, 25.143 g of BPDA (0.0855 mol) was added. After stirring for 2 hours, a small amount of BPDA was used to adjust the viscosity to 250,000±300,000 cps, and finally a copolymer polyamide acid solution with a solid content of 20% was obtained.

[0099] Take out 33 grams of the above copolymerized polyamic acid solution and add 17 grams of N, N-dimethylacetamide (DMAc) to dilute the solid content to 13.2%. After stirring for 10 minutes, dilute acetic anhydride and DMAc at a weight ratio of 5 to 1, and then dilute 3-methylpyridine and DMAc at a weight ratio of 1 to 1, and then add 7.37 grams of acetic anhydride dilution and 5.6 grams of 3-methylpyridine dilution. After uniform stirring, use a centrifugal degasser to degas, apply the degassing solution to the glass plate, and then use a scraper with a gap of 600μm to apply it. Place the coated sample in an 80℃ oven and bake for 40 minutes, then heat it to 170℃ at a speed of 3.6℃ / min and bake it for 10 minutes, then heat it to 260℃ at a speed of 5.9℃ / min and bake it for 10 minutes, and finally heat it to 350℃ at a speed of 8.13℃ / min and bake it for 20 minutes as the final treatment.

[0100] Preparation of laminated board: same as in Example 1.

[0101] <Comparative Example 2>

[0102] Preparation of polyimide film

[0103] 7.167 g of p-phenylenediamine (p-PDA, 0.0663 mole) was added to 400 g of N,N-dimethylacetamide (DMAc). After it was completely dissolved, 11.565 g of 1,2,4,5-benzenetetracarboxylic anhydride (PMDA, 0.0530 mole) was added. The mixture was stirred for 1 hour while the temperature was maintained at 25°C. Then 18.762 g of 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB, 0.0884 mole) was added. The mixture was stirred until it was completely dissolved. Then 0.482 g of pyromellitic anhydride (PMDA, 0.0786 mole) was slowly added. 20.151 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.0685 mole) were stirred for 0.5 hour to dissolve and react, and the temperature of the solution was maintained at 25°C, and then 13.272 g of 4,4'-diaminodiphenyl ether (ODA, 0.00.0663 mol) was added. After it was completely dissolved, 27.626 g of BPDA (0.0939 mol) was added. After stirring and reacting for 2 hours, a small amount of BPDA was used to adjust the viscosity to 250,000±300,000 cps, and finally a copolymer polyamic acid solution with a solid content of 20% was obtained.

[0104] Take out 33 grams of the above copolymerized polyamic acid solution and add 17 grams of N, N-dimethylacetamide (DMAc) to dilute the solid content to 13.2%. After stirring for 10 minutes, dilute acetic anhydride and DMAc at a weight ratio of 5 to 1, and then dilute 3-methylpyridine and DMAc at a weight ratio of 1 to 1, and then add 7.15 grams of acetic anhydride dilution and 5.43 grams of 3-methylpyridine dilution respectively. After uniform stirring, use a centrifugal degasser to degas, apply the degassing solution to the glass plate, and then use a scraper with a gap of 600μm to apply it. Place the coated sample in an 80℃ oven and bake for 40 minutes, then heat it to 170℃ at a speed of 3.6℃ / min and bake it for 10 minutes, then heat it to 260℃ at a speed of 5.9℃ / min and bake it for 10 minutes, and finally heat it to 350℃ at a speed of 8.13℃ / min and bake it for 20 minutes as the final treatment.

[0105] Preparation of laminated board: same as in Example 1.

[0106] <Comparative Example 3>

[0107] Preparation of polyimide film

[0108] 13.272 g of 4,4'-diaminodiphenyl ether (ODA, 0.0663 mole) was added to 400 g of N,N-dimethylacetamide (DMAc). After it was completely dissolved, 11.565 g of pyromellitic anhydride (PMDA, 0.0393 mole) was added. The mixture was stirred for 1 hour while the temperature was maintained at 25°C. Then 18.762 g of 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB, 0.0884 mole) was added. The mixture was stirred until it was completely dissolved. Then 0.482 g of pyromellitic anhydride (PMDA, 0.0022 mole) was slowly added. le), and 20.801 grams of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.0707 mole) were stirred for 0.5 hour to dissolve and react, and the temperature of the solution was maintained at 25°C, and then 7.167 grams of p-phenylenediamine (PDA, 0.0663 mol) was added. After it was completely dissolved, 26.976 grams of BPDA (0.0917 mol) was added. After stirring and reacting for 2 hours, a small amount of BPDA was used to adjust the viscosity to 250,000±300,000 cps, and finally a copolymer polyamic acid solution with a solid content of 20% was obtained.

[0109] Take out 33 grams of the above copolymerized polyamic acid solution and add 17 grams of N, N-dimethylacetamide (DMAc) to dilute the solid content to 13.2%. After stirring for 10 minutes, dilute acetic anhydride and DMAc at a weight ratio of 5 to 1, and then dilute 3-methylpyridine and DMAc at a weight ratio of 1 to 1, and then add 7.15 grams of acetic anhydride dilution and 5.43 grams of 3-methylpyridine dilution respectively. After uniform stirring, use a centrifugal degasser to degas, apply the degassing solution to the glass plate, and then use a scraper with a gap of 600μm to apply. Place the coated sample in an 80℃ oven for 40 minutes, then heat it to 170℃ at a rate of 3.6℃ / min and bake it for 10 minutes, then heat it to 260℃ at a rate of 5.9℃ / min and bake it for 10 minutes, and finally heat it to 350℃ at a rate of 8.13℃ / min and bake it for 20 minutes as the final treatment.

[0110] Preparation of laminated board: same as in Example 1.

[0111] <Comparative Example 4>

[0112] Preparation of polyimide film

[0113] 13.272 g of 4,4'-diaminodiphenyl ether (ODA, 0.0663 mole) was added to 400 g of N,N-dimethylacetamide (DMAc). After it was completely dissolved, 15.601 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.0530 mole) was added. The mixture was stirred for 1 hour while the temperature was maintained at 25°C. Then 18.762 g of 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB, 0.0884 mole) was added. The mixture was stirred until it was completely dissolved. Then 12.047 g of pyromellitic anhydride (PMDA, 0 .0552 mole), and 4.550 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.0155 mole) were stirred for 0.5 hour to dissolve and react, and the temperature of the solution was maintained at 25°C, and then 7.167 g of p-phenylenediamine (PDA, 0.0552 mol) was added. After it was completely dissolved, 27.626 g of BPDA (0.0939 mol) was added. After stirring for 2 hours, a small amount of BPDA was used to adjust the viscosity to 250,000±300,000 cps, and finally a copolymer polyamic acid solution with a solid content of 20% was obtained.

[0114] Take out 33 grams of the above copolymerized polyamic acid solution and add 17 grams of N, N-dimethylacetamide (DMAc) to dilute the solid content to 13.2%. After stirring for 10 minutes, dilute acetic anhydride and DMAc at a weight ratio of 5 to 1, and then dilute 3-methylpyridine and DMAc at a weight ratio of 1 to 1, and then add 7.15 grams of acetic anhydride dilution and 5.43 grams of 3-methylpyridine dilution respectively. After uniform stirring, use a centrifugal degasser to degas, apply the degassing solution to the glass plate, and then use a scraper with a gap of 600μm to apply. Place the coated sample in an 80℃ oven for 40 minutes, then heat it to 170℃ at a rate of 3.6℃ / min and bake it for 10 minutes, then heat it to 260℃ at a rate of 5.9℃ / min and bake it for 10 minutes, and finally heat it to 350℃ at a rate of 8.13℃ / min and bake it for 20 minutes as the final treatment.

[0115] Preparation of laminated board: same as in Example 1.

[0116] <Comparative Example 5>

[0117] Preparation of polyimide film

[0118] 12.985 g of phenylenediamine (PDA, 0.120 mole) was added to 400 g of N,N-dimethylacetamide (DMAc). After all the DMAc was dissolved, 31.797 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.1081 mole) was added. The mixture was stirred for 2 hours while the temperature was maintained at 25°C. 25.493 g of 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB, 0.0120 mole) was added and stirred until the mixture was completely dissolved. The mixture was dissolved in 1% 4-nitropropanediol (26.192 g of pyromellitic anhydride (PMDA, 0.120 mole) and 2.473 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.0084 mole) were slowly added and stirred for 0.5 hour to dissolve and react. The temperature of the solution was maintained at 25°C. After stirring for 2 hours, a small amount of BPDA was used to adjust the viscosity to 250,000±300,000 cps, and finally a copolymer polyamic acid solution with a solid content of 20% was obtained.

[0119] Take out 33 grams of the above copolymerized polyamic acid solution and add 17 grams of N, N-dimethylacetamide (DMAc) to dilute the solid content to 13.2%. After stirring for 10 minutes, dilute acetic anhydride and DMAc at a weight ratio of 5 to 1, and then dilute 3-methylpyridine and DMAc at a weight ratio of 1 to 1, and then add 7.77 grams of acetic anhydride dilution and 5.90 grams of 3-methylpyridine dilution respectively. After uniform stirring, use a centrifugal degasser to degas, apply the degassing solution to the glass plate, and then use a scraper with a gap of 600μm to apply. Place the coated sample in an 80℃ oven for 40 minutes, then heat it to 170℃ at a rate of 3.6℃ / min and bake it for 10 minutes, then heat it to 260℃ at a rate of 5.9℃ / min and bake it for 10 minutes, and finally heat it to 350℃ at a rate of 8.13℃ / min and bake it for 20 minutes as the final treatment.

[0120] Preparation of laminated board: same as in Example 1.

[0121] <Comparative Example 6>

[0122] Preparation of polyimide film

[0123] 25.493 g of 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB, 0.120 mole) was added with 400 g of N,N-dimethylacetamide (DMAc). After it was completely dissolved, 31.797 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.1081 mole) was added. The mixture was stirred for 2 hours while the temperature was maintained at 25°C. 12.985 g of p-phenylenediamine (PDA, 0.120 mole) was added and stirred until it was completely dissolved. The mixture was dissolved in 1% 4-nitropropanediol (26.192 g of pyromellitic anhydride (PMDA, 0.120 mole) and 2.473 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.0084 mole) were slowly added and stirred for 0.5 hour to dissolve and react. The temperature of the solution was maintained at 25°C. After stirring for 2 hours, a small amount of BPDA was used to adjust the viscosity to 250,000±300,000 cps, and finally a copolymer polyamic acid solution with a solid content of 20% was obtained.

[0124] Take out 33 grams of the above copolymerized polyamic acid solution and add 17 grams of N, N-dimethylacetamide (DMAc) to dilute the solid content to 13.2%. After stirring for 10 minutes, dilute acetic anhydride and DMAc at a weight ratio of 5 to 1, and then dilute 3-methylpyridine and DMAc at a weight ratio of 1 to 1, and then add 7.77 grams of acetic anhydride dilution and 5.90 grams of 3-methylpyridine dilution respectively. After uniform stirring, use a centrifugal degasser to degas, apply the degassing solution to the glass plate, and then use a scraper with a gap of 600μm to apply. Place the coated sample in an 80℃ oven for 40 minutes, then heat it to 170℃ at a rate of 3.6℃ / min and bake it for 10 minutes, then heat it to 260℃ at a rate of 5.9℃ / min and bake it for 10 minutes, and finally heat it to 350℃ at a rate of 8.13℃ / min and bake it for 20 minutes as the final treatment.

[0125] Preparation of laminated board: same as in Example 1.

[0126] <Comparative Example 7>

[0127] Preparation of polyimide film

[0128] 22.954 g of 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB, 0.108 mole) was added with 400 g of N,N-dimethylacetamide (DMAc). After all the DMAc was dissolved, 28.631 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.108 mole) was added. The mixture was stirred for 2 hours while the temperature was maintained at 25°C. 21.650 g of 4,4'-diaminodiphenyl ether (ODA, 0.0108 mole) was added and stirred until the mixture was completely dissolved. After the mixture is completely dissolved, 23.584 g of pyromellitic anhydride (PMDA, 0.108 mole) and 2.227 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.0076 mole) are slowly added and stirred for 0.5 hour to allow them to dissolve and react. The temperature of the solution is maintained at 25°C. After stirring and reacting for 2 hours, a small amount of BPDA is used to adjust the viscosity to 250,000±300,000 cps, and finally a copolymerized polyamide acid solution with a solid content of 20% is obtained.

[0129] Take out 33 grams of the above copolymerized polyamic acid solution and add 17 grams of N, N-dimethylacetamide (DMAc) to dilute the solid content to 13.2%. After stirring for 10 minutes, dilute acetic anhydride and DMAc at a weight ratio of 5 to 1, and then dilute 3-methylpyridine and DMAc at a weight ratio of 1 to 1, and then add 6.99 grams of acetic anhydride dilution and 5.32 grams of 3-methylpyridine dilution respectively. After uniform stirring, use a centrifugal degasser to degas, apply the degassing solution to the glass plate, and then use a scraper with a gap of 600μm to apply. Place the coated sample in an 80℃ oven for 40 minutes, then heat it to 170℃ at a rate of 3.6℃ / min and bake it for 10 minutes, then heat it to 260℃ at a rate of 5.9℃ / min and bake it for 10 minutes, and finally heat it to 350℃ at a rate of 8.13℃ / min and bake it for 20 minutes as the final treatment.

[0130] Preparation of laminated board: same as in Example 1.

[0131] <Comparative Example 8>

[0132] Preparation of polyimide film

[0133] 22.954 g of 2,2'-dimethyl-4,4'-diaminobiphenyl (PDA, 0.0449 mole) was added with 400 g of N,N-dimethylacetamide (DMAc). After all the DMAc was dissolved, 11.901 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.0404 mole) was added. The mixture was stirred for 1 hour while the temperature was maintained at 25°C. 19.082 g of 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB, 0.0899 mole) and 2.430 g of p-phenylenediamine (0.0225 mole) were added. The mixture was stirred until all the DMAc was dissolved. 17.15 g of BPDA was added slowly. 5 g of PMDA (0.0786 mole) and 6.611 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA, 0.0225 mole) were stirred for 1 hour and then 13.499 g of 4,4'-diaminodiphenyl ether (ODA, 0.0674 mole) was added. After the ODA was completely dissolved, 23.470 g of BPDA (0.0798 mole) was added. The mixture was stirred for 2 hours and the temperature of the solution was maintained at 25°C. Finally, a trace amount of BPDA was used to adjust the viscosity to 250,000±300,000 cps, and a copolymer polyamide acid solution with a solid content of 20% was finally obtained.

[0134] Take out 33 grams of the above copolymerized polyamic acid solution and add 17 grams of N, N-dimethylacetamide (DMAc) to dilute the solid content to 13.2%. After stirring for 10 minutes, dilute acetic anhydride and DMAc at a weight ratio of 5 to 1, and then dilute 3-methylpyridine and DMAc at a weight ratio of 1 to 1, and then add 7.27 grams of acetic anhydride dilution and 5.52 grams of 3-methylpyridine dilution respectively. After uniform stirring, use a centrifugal degassing machine to degas, apply the degassing solution to the glass plate, and then use a scraper with a gap of 600μm to apply. Place the coated sample in an 80℃ oven for 40 minutes, then heat it to 170℃ at a rate of 3.6℃ / min and bake it for 10 minutes, then heat it to 260℃ at a rate of 5.9℃ / min and bake it for 10 minutes, and finally heat it to 350℃ at a rate of 8.13℃ / min and bake it for 20 minutes as the final treatment.

[0135] Preparation of laminated board: same as in Example 1.

[0136] Examples and comparative examples:

[0137]

[0138]

[0139] The description of the above embodiments is only used to help understand the method and core idea of ​​the present application. It should be noted that, for ordinary technicians in this technical field, several improvements and modifications can be made to the present application without departing from the principles of the present application, and these improvements and modifications also fall within the scope of protection of the claims of the present application.

Claims

1. A polyimide film, made of a copolymerized polyimide formed by a dianhydride and a dianhydride, wherein the dianhydride comprises 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), accounting for 60-80 mol% of the total dianhydride moles, and pyromellitic anhydride (PMDA), accounting for 20-40 mol% of the total dianhydride moles; The diamines include p-phenylenediamine (p-PDA) accounting for 10-40 mol% of the total diamine moles, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB) accounting for 30-60 mol% of the total diamine moles, and 4,4'-diaminodiphenyl ether (ODA) accounting for 10-40 mol% of the total diamine moles; in, The copolymerized polyimide has a copolymer segment composed of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) and p-phenylenediamine (p-PDA), and the copolymer segment accounts for 25-40% of the total molar number of the polyimide, so that the thermal linear expansion coefficient CTE of the polyimide film is less than 15ppm / ℃ and the Young's modulus is greater than 7GPa.

2. The polyimide film according to claim 1, wherein The molar ratio of dianhydride to diamine in the copolymer segment composed of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) and p-phenylenediamine (p-PDA) is greater than 0.

9.

3. The polyimide film according to claim 1, wherein The polyimide film is made by a chemical cyclization method, and its baking temperature is between 350°C and 380°C.

4. A laminate comprising a polyimide film as claimed in any one of claims 1 to 3 and a metal layer attached to the polyimide film, wherein the bonding strength between the metal layer and the polyimide film is greater than 0.65 Kgf / cm, and the bonding strength is still greater than 0.5 Kgf / cm after baking at 150°C for at least 24 hours. 5 . The laminate according to claim 4 , wherein the polyimide film is surface treated using plasma so that the adhesion between the metal layer and the polyimide film is greater than 0.8 Kgf / cm. The laminate according to claim 5 , wherein the plasma surface treatment is atmospheric plasma.

7. The laminate according to claim 6, wherein the atmospheric plasma uses a gas selected from one or more of nitrogen, argon, oxygen and carbon tetrafluoride.